Latest resources [electronic resource] - Stanford University Libraries (Los Gatos, CA HighWire Press, Inc., 2020)
A division of the Stanford University Libraries, HighWire Press hosts a large repository of high impact, peer-reviewed content, with 1079 journals and 4,552,400 full text articles from over 130 scholarly publishers. HighWire-hosted publishers have collectively made 1,823,449 articles free. You will find the journals in the Open Science Directory with the embargo information included.
UPMindanao, University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; Periodicals -- Electronic information resources; Periodicals -- Open access publishing